2012
DOI: 10.1002/jmri.23886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the tibial tunnel after intraoperatively administered platelet‐rich plasma gel during anterior cruciate ligament reconstruction using diffusion weighted and dynamic contrast‐enhanced MRI

Abstract: Purpose: To evaluate effect of platelet-rich plasma gel (PRPG), locally administered during the anterior cruciate ligament (ACL) reconstruction, with two MRI methods. The proximal tibial tunnel was assessed with diffusion weighted imaging (DWI) and with dynamic contrastenhanced imaging (DCE-MRI). Materials and Methods:In 50 patients, standard arthroscopic ACL reconstructions were performed. The patients in the PRPG group (n ¼ 25) received a local application of PRPG. The proximal tibial tunnel was examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 36 publications
(94 reference statements)
0
54
0
Order By: Relevance
“…Finally, with regard to positive PRP effects, Rupreht et al were the only ones documenting benefit in the bony tunnel/graft area. In a randomized study [ 47 ] they showed that PRP administration reduced edema around the tibial tunnel during the first postoperation month and also increased vascular density and microvessel permeability in the proximal tibial tunnel at 1 and 2.5 months' MRI evaluation, thus suggesting that PRP is most effective in the early phases of healing. In another paper [ 43 ], the same authors reported that PRP increased cortical bone formation around the tibial tunnel wall at 6 months followup, thus suggesting that PRP might effectively contribute to graft-bone integration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with regard to positive PRP effects, Rupreht et al were the only ones documenting benefit in the bony tunnel/graft area. In a randomized study [ 47 ] they showed that PRP administration reduced edema around the tibial tunnel during the first postoperation month and also increased vascular density and microvessel permeability in the proximal tibial tunnel at 1 and 2.5 months' MRI evaluation, thus suggesting that PRP is most effective in the early phases of healing. In another paper [ 43 ], the same authors reported that PRP increased cortical bone formation around the tibial tunnel wall at 6 months followup, thus suggesting that PRP might effectively contribute to graft-bone integration.…”
Section: Resultsmentioning
confidence: 99%
“…The application of PRP has been hypothesized to improve graft integration within the tunnels. Concerning the osteoligamentous integration, Rupreht et al showed increased vascular density and microvessel permeability in the proximal tibial tunnel at 1 and 2.5 months' MRI evaluation, as well as reduced bone edema around the tunnel and increased cortical bone formation around the tibial tunnel wall at 6 months followup [ 43 , 47 ]. Vogrin et al [ 49 ] also showed a significantly higher neovascularization 4–6 weeks after PRP administration, but the advantage of PRP was not confirmed at further followup, thus suggesting that PRP is most effective in the early phases of healing.…”
Section: Discussionmentioning
confidence: 99%
“…Two DWI acquisitions with different b values enable calculation of ADC map. Higher ADC values correspond to elevated diffusion in the extracellular space; the motion of water is less restricted [ 20 ]. In areas with high cellularity, molecular water mobility is impeded, yielding lower ADC values [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher ADC values correspond to elevated diffusion in the extracellular space; the motion of water is less restricted [ 20 ]. In areas with high cellularity, molecular water mobility is impeded, yielding lower ADC values [ 20 ]. One of the most important findings of this study is the feasibility of DWI-MRI to detect subtle, activity-related changes in the growth plates around the knees of adolescent soccer players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation